2021
DOI: 10.1038/s41598-021-02207-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro response of vanilla (Vanilla planifolia Jacks. ex Andrews) to PEG-induced osmotic stress

Abstract: Drought-induced water stress affects the productivity of the Vanilla planifolia Jacks. ex Andrews crop. In vitro culture technique is an effective tool for the study of water stress tolerance mechanisms. This study aimed to evaluate the morphological, physiological and biochemical response of V. planifolia under in vitro water stress conditions induced with polyethylene glycol (PEG). In vitro regenerated shoots of 2 cm in length were subjected to different concentrations of PEG 6000 (0, 1, 2 and 3% w/v) using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 63 publications
0
7
0
3
Order By: Relevance
“…On the other hand, Liao et al [ 57 ] observed that mycorrhizae ( Glomus lamellosum and Glomus etunicatum ) at different doses (0, 60, 120, 180, and 240 spores per plant) and a 2-week period of drought stress had no significant effect on the protein content of C. migao . The increase in protein content could be a drought stress tolerance response and represent the synthesis of hydrophilins, aquaporins (AQP), dehydrins, antioxidant enzymes, and chaperonins as tolerance mechanisms against drought stress [ 58 ]. AMF symbiosis specifically induces the expression of genes and protein transporters associated with a drought stress tolerance response; these include AQPs, inorganic phosphorus transporters, and ammonium, nitrate, sulfur, zinc, and carbon transporters [ 7 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Liao et al [ 57 ] observed that mycorrhizae ( Glomus lamellosum and Glomus etunicatum ) at different doses (0, 60, 120, 180, and 240 spores per plant) and a 2-week period of drought stress had no significant effect on the protein content of C. migao . The increase in protein content could be a drought stress tolerance response and represent the synthesis of hydrophilins, aquaporins (AQP), dehydrins, antioxidant enzymes, and chaperonins as tolerance mechanisms against drought stress [ 58 ]. AMF symbiosis specifically induces the expression of genes and protein transporters associated with a drought stress tolerance response; these include AQPs, inorganic phosphorus transporters, and ammonium, nitrate, sulfur, zinc, and carbon transporters [ 7 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Y finalmente desde un punto de vista social ya que el cultivo de la vainilla se puede beneficiar a los pequeños productores obteniendo grandes ingresos económicos a través de estrategias de planeación y transferencias de tecnología (Borbolla-Pérez et al, 2017). La vainilla al ser un cultivo clonal se encuentra fuertemente amenazada por factores de estrés tanto bióticos (Hongos; Colletotrichum orchidophilum (Charron et al, 2018), Colletotrichum gloeosporoides (Guevara-Suarez et al, 2022) y Fusarium (Ramírez-Mosqueda et al, 2019), como abióticos (sequía) (Iglesias-Andreu et al, 2021;Martínez-Santos et al, 2021). Esto es debido a la ausencia de diversidad genética que permita aumentar la probabilidad de supervivencia con la presencia de genes que respondan de manera favorable a situaciones de estrés que afecte a las plantas morfo-fisiológicamente, derivando en problemas como aborción floral y/o de frutos, cierre estomático, reducción de la tasa fotosintética, inhibición del crecimiento, reducción del área foliar, deshidratación severa, aumento en la susceptibilidad de patógenos y por último necrosis (Borbolla-Pérez et al, 2016).…”
Section: Características Del Cultivo Y Producción De Vanilla Planifoliaunclassified
“…Por lo que es en este sentido que el sistema de conservación in vitro por medio del cultivo de tejidos vegetales que se puede optar por la ruta de la conservación de germoplasma de vainilla con especial interés ante diferentes factores de producción, resistencia, tolerancia, etc. (Gantait, 2017;Martínez-Santos et al, 2021;Pastelín-Solano et al, 2019;.…”
Section: Conservación De Vanilla Planifoliaunclassified
“…The carbohydrates are considered a significant component for the storage medium since the use of osmotically active substances can lower the osmotic potential of the substrate, modify the growth of the shoots and affect the storage time [ 51 ].…”
Section: Factors Affecting Sgs Of Shoot Cultures Of Temperate Fruit C...mentioning
confidence: 99%